Sports-related concussion history, reporting behaviours, knowledge, and attitudes in Pakistani university student-athletes - Mahfooz, Masood; Noh, Young-Eun; Teo, Eng Wah; Savila, Zubia (Journal of the Pakistan Medical Association, 2024)
Objective: To assess student-athletes’ knowledge and attitudes towards sport-related concussions and to investigate concussion history and reporting behaviours. Method: The cross-sectional, survey-based study was conducted from September 2020 to June 2021 after approval from the research ethics committee of Universiti Malaya, Malaysia, and comprised student-athletes of either gender aged 18 years or above at various universities across Pakistan and who played contact or collision sports for their universities. Data was collected using the Urdu version of the Rosenbaum Concussion Knowledge and Attitudes Survey-Student Version. Data was also gathered about the participants’ self-reported exposure to formal concussion education, previous sport-related concussion history, and reporting behaviours, where applicable. Data was analysed using SPSS 23. Results: Of the 369 participants, 224(60.7%) were males and 145(39.3%) were females. The overall mean age was 19.95±1.75 years. Among the participants, 327(88.6%) had not received formal concussion education. The mean knowledge score was 12.76±2.73 out of a possible 25 points, and the mean attitude score was 38.63±10.30 out of 75 points. Knowledge had a weak positive correlation with attitude towards sport-related concussions SRC (p<0.05). Females displayed better attitudes towards sport-related concussions than their male counterparts (p<0.05). Overall, 126(34%) participants had experienced sport-related concussion symptoms following a blow to the head in the preceding 12 months, and 81(64.3%) of them had continued playing while being symptomatic. Conclusion: Pakistani university student-athletes lacked adequate concussion knowledge and held poor attitudes towards sport-related concussions. Key Words: Brain concussions, Brain injuries, Traumatic, Athletes, Incidence.